2015
DOI: 10.1186/s12890-015-0057-4
|View full text |Cite
|
Sign up to set email alerts
|

A double blind randomized placebo control crossover trial on the effect of dietary nitrate supplementation on exercise tolerance in stable moderate chronic obstructive pulmonary disease

Abstract: BackgroundDietary nitrate supplementation has been shown to decrease the oxygen cost of exercise and prolong exercise tolerance, as measured by sub-maximal exercise endurance distance and time at 85% V̇O2max, in both elite athletes and normal healthy subjects. Patients with chronic obstructive pulmonary disease (COPD) have reduced quality of life and ability to perform activities of daily living attributable to diminished exercise tolerance, and dietary nitrate may be able to ameliorate this.MethodsWe performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 35 publications
(38 reference statements)
1
41
0
Order By: Relevance
“…Conversely, in a different study, after a 6-day trial of beetroot juice consumption, distance on the 6MWT did not improve [40]. Similar results were observed in another acute dietary nitrate supplementation intervention that described similar ESWT distance and time to fatigue between active and placebo in the same population [64]. Notably, longer supplementation with beetroot juice (8 days) showed similar results with no improvements in peak VO 2 [41].…”
Section: Dietary Nitrate Supplementation In Copdmentioning
confidence: 58%
See 1 more Smart Citation
“…Conversely, in a different study, after a 6-day trial of beetroot juice consumption, distance on the 6MWT did not improve [40]. Similar results were observed in another acute dietary nitrate supplementation intervention that described similar ESWT distance and time to fatigue between active and placebo in the same population [64]. Notably, longer supplementation with beetroot juice (8 days) showed similar results with no improvements in peak VO 2 [41].…”
Section: Dietary Nitrate Supplementation In Copdmentioning
confidence: 58%
“…?? Dietary Nitrates [39][40][41]63,64] ↔ ↔ ↑ Nutrition Support Supplements [45][46][47]49,50] ?? ↔ ↔…”
Section: Summary Of Nutrition Interventions In Copdmentioning
confidence: 99%
“…Leong et al . found no effect of 3 days of beetroot juice (4.8 mmol twice a day) on the endurance shuttle walk test (ESWT) distance and time to fatigue at 85% VO 2,max in 19 patients with COPD . Whilst Curtis et al .…”
Section: Does Nitrite Alter Mitochondrial Metabolism?mentioning
confidence: 99%
“…Using the 6MWT, Shepherd et al did not find any effect of beetroot juice on the oxygen cost of exercise or distance covered in 13 patients with COPD [28]. Leong et al found no effect of 3 days of beetroot juice (4.8 mmol twice a day) on the endurance shuttle walk test (ESWT) distance and time to fatigue at 85% VO 2,max in 19 patients with COPD [29]. Whilst Curtis et al did not find any effect on endurance time at 70% of maximal workload of beetroot juice (12.9 mmol nitrate) ingested 3 hours beforehand, isotime oxygen consumption (VO 2 ) was 3-4% lower following nitrate supplementation [30].…”
Section: Does Nitrite Alter Mitochondrial Metabolism?mentioning
confidence: 99%
“…One study found no differences in blood pressures or six-minute walk distance whereas the other study showed an increase in median sub-maximal constant work rate exercise time of 28.8 seconds and lower diastolic blood pressures during exercise. Two other recent published studies in COPD have similarly conflicting results [11,12].…”
mentioning
confidence: 85%